1979
DOI: 10.1084/jem.149.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Disproportion in T-cell subpopulations in immunodeficient mutant hr/hr mice.

Abstract: Mice of the HRS strain, which carry the mutant gene hr, were examined for abnormalities in representation of the three T-cell sets Ly1, Ly23, and Ly123 in the spleen. The salient feature of hr/hr mice, which are immunologically deficient, in comparison with +/hr segregants, was a gross disproportion in numbers of cells belonging to the Ly1 and Ly123 sets, at the age of 3--3.5 mo. At this age, Ly123 cells of hr/hr spleen outnumbered Ly1 cells by 2:1, whereas in +/hr spleens Ly123 cells were outnumbered by appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…A slightly depressed Thy1.2 expression was evident only the day after the last DES treatment. Irrespective of neonatal treatment the cytotoxicity index (CI; Thy1.2 antibodies) in splenocyte suspensions from 12-wk-old and 1-yr-old females was higher than in suspensions from 8-wk-old females, which is in line with an earlier described age-related increase in the spleen Thy1+ cell population (Reske-Kunz et al, 1979;Kalland, 1980). In old mice (40 wk) the spleen Thy1+ population was found to be decreased (Yoshikai et al, 1988), which is contrary to our findings of a stable level of Thy1.2-related CI in spleens from 12-wk-old and 1-yr-old females.…”
Section: Discussionsupporting
confidence: 76%
“…A slightly depressed Thy1.2 expression was evident only the day after the last DES treatment. Irrespective of neonatal treatment the cytotoxicity index (CI; Thy1.2 antibodies) in splenocyte suspensions from 12-wk-old and 1-yr-old females was higher than in suspensions from 8-wk-old females, which is in line with an earlier described age-related increase in the spleen Thy1+ cell population (Reske-Kunz et al, 1979;Kalland, 1980). In old mice (40 wk) the spleen Thy1+ population was found to be decreased (Yoshikai et al, 1988), which is contrary to our findings of a stable level of Thy1.2-related CI in spleens from 12-wk-old and 1-yr-old females.…”
Section: Discussionsupporting
confidence: 76%
“…In Leishmania- Furthermore Hairless mice exhibit a mild immunodeficiency, associated with abnormalities in T-cells (Morrisey et al, 1980;Rezke-Kunz et al, 1979). Zarach et al (2004) showed that the Hr gene encodes a protein highly expressed in skin and brain, which acts as a transcriptional co-repressor for some nuclear receptors such as thyroid hormone, retinoic acid, and vitamin D receptors.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Animals with this genotype also possess a quantitative deficiency of T lymphocytes; specifically, the ratio between Ly1 and Ly123 lymphocytes is reversed in the spleens of 3-to 3.5-month-old mice, without affecting the total lymphocytes counts (31). These animals have a defect in the proliferative response to alloantigens but no defect in mitogenic responses or lymphocyte cytotoxicity (25).…”
Section: Discussionmentioning
confidence: 99%